Preliminary outcomes of endoscopic middle-ear surgery in 103 cases: a UK experience. Issue 6 (18th July 2018) - Yiannakis, C P; Sproat, R; Iyer, A
Abstract: Background: Totally endoscopic ear surgery and endoscope-assisted microsurgery are still new concepts, with relatively few centres in the UK performing them. Advantages include better visualisation of difficult to reach areas, such as the sinus tympani, and limited external incisions. This paper reports our short-term outcomes for endoscopic middle-ear surgery. Methods: A prospective review was conducted of the first 103 consecutive patients undergoing totally endoscopic ear surgery or endoscope-assisted microsurgery in 1 centre performed by 1 operator. The outcomes assessed were: tympanic membrane healing, audiological data and complications. Results: Twenty-five patients underwent endoscope-assisted microsurgery, while 78 had totally endoscopic ear surgery. There were no reported cases of dead ear or permanent facial nerve palsy. The average air–bone gap following stapedectomy was 7.38 dB. The tympanic membrane healing rate was 89 per cent. Conclusion: Our results confirm that endoscopic middle-ear surgery is safe, and the short-term outcomes are comparable with conventional surgery.